2020
DOI: 10.3390/ma14010130
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Dextranase on Nano-Hydroxyapatite as a Recyclable Catalyst

Abstract: The immobilization technology provides a potential pathway for enzyme recycling. Here, we evaluated the potential of using dextranase immobilized onto hydroxyapatite nanoparticles as a promising inorganic material. The optimal immobilization temperature, reaction time, and pH were determined to be 25 °C, 120 min, and pH 5, respectively. Dextranase could be loaded at 359.7 U/g. The immobilized dextranase was characterized by field emission gun-scanning electron microscope (FEG-SEM), X-ray diffraction (XRD), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…With the adsorption of the enzyme at 1377.83 cm −1 and at 1299.89 cm −1 , a new band appeared that belongs to the C–O and C–N stretching vibrations. This result indicated that a new carboxylic acid group was generated by enzyme immobilization [ 12 , 53 ]. Omnic 9.2 software was used to plot FT–IR spectrum from 800 cm −1 to 2000 cm −1 , and the vibration band in the spectrum can be seen more clearly.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the adsorption of the enzyme at 1377.83 cm −1 and at 1299.89 cm −1 , a new band appeared that belongs to the C–O and C–N stretching vibrations. This result indicated that a new carboxylic acid group was generated by enzyme immobilization [ 12 , 53 ]. Omnic 9.2 software was used to plot FT–IR spectrum from 800 cm −1 to 2000 cm −1 , and the vibration band in the spectrum can be seen more clearly.…”
Section: Resultsmentioning
confidence: 99%
“…Immobilization of enzymes improves their applicability [ 8 ] and storage [ 9 ]. Several carriers, such as alginate [ 10 ], chitin [ 11 ], agarose [ 1 ], and hydroxyapatite [ 12 ], have been used to immobilize dextranase. Although the immobilization rate of the immobilized dextranase has been improved, the stability and reusability of the immobilized enzymes are still not adequate for practical applications; therefore, identifying suitable immobilized materials continues to be the focus of research [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…PsDex1711 is an endodextranase that hydrolyzes the α- (1,6) bond in dextran from the inside to reduce its molecular weight. In contrast, exodextranase cut outward from the reducing end to release glucose [31]. Most dextran anhydrases reported are endotangent dextran anhydrases, and the product formed (i.e., IMOs) has a crucial application value.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-inflammatory drug ibuprofen, the antibiotics norfloxacin and vancomycin, the bisphosphonate alendronate, the cardiovascular drug carvedilol, the anticancer drug cis-diamminedichloroplatinum (II), the di(ethylenediamineplatinum) medronate, and others have all been carried by nano-hydroxyapatite (Nur Farahiyah et al 2014 ). Additionally, nano-hydroxyapatite was used to effectively stabilize these enzymes with a straightforward uptake protocol while maintaining their catalytic activity for the immobilization of β-glucosidase, protease, and phytase with industrial applications as well as dextranase, which is involved in the breakdown of dental plaque (Coutinho et al 2018 ; Zdarta et al 2015 ; Coutinho et al 2020 ; Ding et al 2020 ). A different study used the hydroxyapatite drug composition to release amoxicillin to treat bone infections (Prasanna et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%